2022
DOI: 10.1021/acsami.2c04331
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective Photocatalytic Radical Reactions Triggered by a Photoactive Metal–Organic Framework

Abstract: On account of their inherent reactive properties, radical reactions play an important role in organic syntheses. The booming photochemistry provides a feasible approach to trigger the generation of radical intermediates in organic reaction processes. Thus, developing effective photocatalysts becomes the key step in radical reactions. In this work, the triphenylamine moiety with photoactivity is successfully embedded in a highly porous and stable metal–organic framework (MOF), and the obtained MOF, namely, Zr-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…The activation of dioxygen may be promoted by the diphenylamine units as recently shown for a Zr-based containing similar organic strut. 22 However, in this system, only the formation of the radical O 2 − was observed, which supports the participation of the anthraquinone core of H 4 L, since 1 O 2 was indicated.…”
Section: ■ Results and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The activation of dioxygen may be promoted by the diphenylamine units as recently shown for a Zr-based containing similar organic strut. 22 However, in this system, only the formation of the radical O 2 − was observed, which supports the participation of the anthraquinone core of H 4 L, since 1 O 2 was indicated.…”
Section: ■ Results and Discussionsupporting
confidence: 66%
“…Finally, the use of t BuOH did not lead to a strong suppression of the conversion, suggesting that hydroxyl radicals do not play a decisive role in the mechanism. The activation of dioxygen may be promoted by the diphenylamine units as recently shown for a Zr-based containing similar organic strut . However, in this system, only the formation of the radical O 2 – was observed, which supports the participation of the anthraquinone core of H 4 L, since 1 O 2 was indicated.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, almost quantitative NMR yield (99%) was obtained for the formation of oxindole 3a in acetonitrile, which proceeded via cascade trifluoromethylation/cyclization. Importantly, this protocol is highly selective as the competitive processes such as atom transfer radical addition (ATRA) of alkenes , and direct C–H trifluoromethylation of arenes , were inhibited completely. Further optimization of bases revealed that NaHCO 3 was optimal in which 3a was furnished in 92% isolated yield (entries 6–10, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The photogenerated electrons reduce CF 3 SO 2 Cl (−0.18 V vs SCE) to form the CF 3 radical accompanied with sulfur dioxide and the chloride ion (Figures S6 and S7). The electrophilic CF 3 radical then adds to the terminal olefin of 1a , which induces a subsequent cyclization to afford B ( 1a → A → B ). Finally, single-electron oxidation of unstable arene radical species ( B ) by photoexcited holes yields trifluoromethylated oxindole 3a after the release of a proton.…”
Section: Resultsmentioning
confidence: 99%
“…1 belongs to the monoclinic P 2 1 space group, with the asymmetric unit consisting of two crystallographically independent Ni II ions, two N-containing tipa ligands, two fully deprotonated p-bdc 2– ligands, and four coordinated and one free H 2 O molecules (Table and Figure S1a). Each Ni 2+ ion is connected by three N atoms from distinct tipa ligands as well as three O atoms from one p-bdc 2– and two coordinated H 2 O molecules. All of the Ni–N and Ni–O distances are in the reasonable ranges (Table S3). Bond-valence-sum (BVS) calculations give values of 2.06 and 2.16 for Ni atoms, which are consistent with the expected valence.…”
Section: Resultsmentioning
confidence: 99%